2007
DOI: 10.1200/jco.2006.09.3260
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Clinical Implications of Transformation of Follicular Lymphoma to Diffuse Large B-Cell Lymphoma

Abstract: Advanced stage and high-risk FLIPI and IPI scores at diagnosis correlate with an increased risk of HT. This event strongly influences the outcome of patients with FL by shortening their survival. There may be a subgroup of patients in whom HT does not occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
321
6
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(349 citation statements)
references
References 31 publications
20
321
6
2
Order By: Relevance
“…We observed a transformation rate of 21% among our patients, which is in line with the known histologic transformation rate of follicular lymphoma [13]. Haas et al [9] reported 9% of their patients had transformation to diffuse large B-cell lymphoma.…”
Section: Discussionsupporting
confidence: 72%
“…We observed a transformation rate of 21% among our patients, which is in line with the known histologic transformation rate of follicular lymphoma [13]. Haas et al [9] reported 9% of their patients had transformation to diffuse large B-cell lymphoma.…”
Section: Discussionsupporting
confidence: 72%
“…Transformation from follicular lymphoma into an aggressive lymphoma, usually diffuse large B-cell lymphoma, occurs at a rate of 3% per year. 24 Conconi et al 25 reported histologic transformation in 26% at 14 years in a series of 281 cases treated in Switzerland. In our series, we observed concomitance of diffuse large B-cell lymphoma with follicular lymphoma in 7 (4%) patients at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 97%
“…Majority of our patients were treated with CHOP and 33 of them achieved CR. Transformation to more aggressive lymphoma is known to occur in 10-60 % of the cases [10,11], however it was not documented in any of the 34 cases during the follow up.…”
Section: Discussionmentioning
confidence: 84%